Effects of increasing glycerol and dried distillers grains with solubles on the growth performance and carcass characteristics of finishing pigs - A W Duttlinger; J M Benz; Terry A Houser; Michael D Tokach; Steven S Dritz; K J Prusa; Joel M DeRouchey; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 2008)
A total of 1,160 barrows (PIC, initially 68.4 lb) were used in a 97-d study to determine the influence of glycerol and dried distillers grains with solubles (DDGS) on growing-finishing pig performance, carcass characteristics, and fat quality. Pigs were blocked by weight and randomly allotted to 1 of 6 dietary treatments with 7 replications per treatment. Pigs were fed corn-soybean meal-based diets arranged in a 2 × 3 factorial with main effects of glycerol (0, 2.5, or 5%) and DDGS (0 or 20%). Overall (d 0 to 97), there were no glycerol × DDGS interactions (P>0.12) for growth performance, carcass characteristics, and carcass fat iodine value (IV). Increasing glycerol did not affect (P>0.14) ADG or F/G. Adding 20% DDGS to the diet did not affect ADG. However, pigs fed diets with 20% added DDGS had greater (P<0.02) ADFI resulting in poorer (P<0.01) F/G than pigs fed diets with no DDGS. For carcass characteristics, pigs fed increasing glycerol tended to have increased (linear, P<0.11) yield. Pigs fed diets with added DDGS had increased (P<0.01) jowl fat, belly fat, and backfat IV compared with pigs fed diets with no DDGS. However, increasing dietary glycerol tended to decrease (linear, P<0.11) backfat IV. In conclusion, feeding pigs 20% DDGS worsened F/G and increased carcass fat IV, whereas feeding glycerol did not influence growth performance but tended to improve carcass yield and reduce backfat IV.; Swine Day, 2008, Kansas State University, Manhattan, KS, 2008
Keywords: Swine day; 2008; Kansas Agricultural Experiment Station contribution; no. 09-074-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1001; Dried distiller grains with solubles; Glycerol; Growing-finishing pig